PENDAMPINGAN KEBERLANJUTAN PENGELOLAAN SAMPAH RW I KELURAHAN MANYARAN KOTA SEMARANG - Rukuh Setiadi; Jawoto Sih Setyono; Artiningsih Artiningsih; Mohammad Muktiali; Mada Sophianingrum; Reny Yesiana (Fakultas Teknik Universitas Diponegoro, 2019)
An increase in the level of public consumption will affect the yield of waste (waste), one of which is a solid waste (garbage). in addition, technological developments also have an impact on the quantity of production of waste types. The use of plastic waste in daily life cannot be abandoned, because all products of daily necessities cannot be separated from plastic/bottle wrap. Natural decomposition of plastic waste takes a long time, so there is a need for sustainable waste management as done by the people of Manyaran Village. The waste management action in Manyaran Village is not only the responsibility of the kelurahan level but also at the RW level which has begun to initiate waste sorting.Manyaran Village is one of the assisted areas of the City and Regional Planning Department, Faculty of Engineering, Diponegoro University, in terms of environmental management towards the thematic village of waste sorting. During the 3 years period, Undip worked with NGO Mercy Corp Indonesia to assist the community in waste management and now is the fourth year in community assistance in waste management. Based on the results of community aspirations, the need for waste management for 2019 is the use of plastic waste to make eco brick. Ecobrick is a building brick made from plastic waste where its use can be used repeatedly.The target of this community service activity is to make eco brick a useful form, for example, chairs, tables. The expected outcome of this service activity is to make the Manyaran Village as a target area of the Regional and City Planning Department, Faculty of Engineering, Diponegoro University.